Sustainable development disparities in the EU-27 based on R&D and innovation factors - Marius Constantin; Mihai Dinu; Simona Roxana Pătărlăgeanu; Cristian Chelariu (Amfiteatru Economic Journal, 2021)
Ever since it was adopted in 2015 by the United Nations, the 2030 Agenda for Sustainable Development has acted as the main guideline for European Union Member States in regard to achieving economic prosperity, environmental sustainability and peaceful, inclusive and innovative societies. However, in the race for sustainable development, some European Union Member States are ahead of the others - not only as far as meeting the Sustainable Development Goals is concerned, but from the perspective of the R&D and innovation factors as well. In this context, the objective of this research was to explore sustainable development disparities between the EU-27 Members, based on the previously mentioned factors. A cross-sectional multiple linear regression model was constructed to facilitate an in-depth look at the observations. The econometric analysis was carried out based on the Global SDG Index, the Global Innovation Index and on the percentage of the GDP allocated to R&D activities. Although the transition to the sustainable development model requires modern and disruptive approaches at country level, the literature is not rich on papers fully covering the nature of the existing links between the variables analyzed in the proposed econometric model. Results show that countries from Northern and Westeren Europe are leading the change to a more innovative and sustainable path for the European Union. This implies the responsibility of high levels of R&D expenditure. Although no European country is on track on meeting the Sustainable Development Goals, Central and Eastern European Countries have made a lot of catching up to the Northwestern European leaders. The results of this research help decision-makers improve their strategies by understanding the impact of R&D and innovation factors on meeting sustainable development throughout EU-27 at an equitable pace for all European members.
Keywords: Q01; C21; 330; sustainability; sustainable development disparities; research and development; innovation; budgetary allocation; policy harmonization